NF-κB c-Rel Is Dispensable for the Development but Is Required for the Cytotoxic Function of NK Cells - Vicioso, Yorleny; Wong, Derek P.; Roy, Nand K.; Das, Nayanika; Zhang, Keman; Ramakrishnan, Parameswaran; Parameswaran, Reshmi (Frontiers in Immunology, 2021)
Natural Killer (NK) cells are cytotoxic lymphocytes critical to the innate immune system. We found that germline deficiency of NF-κB c-Rel results in a marked decrease in cytotoxic function of NK cells, both in vitro and in vivo, with no significant differences in the stages of NK cell development. We found that c-Rel binds to the promoters of perforin and granzyme B, two key proteins required for NK cytotoxicity, and controls their expression. We generated a NK cell specific c-Rel conditional knockout to study NK cell intrinsic role of c- Rel and found that both global and conditional c-Rel deficiency leads to decreased perforin and granzyme B expression and thereby cytotoxic function. We also confirmed the role of c-Rel in perforin and granzyme B expression in human NK cells. c-Rel reconstitution rescued perforin and granzyme B expressions in c-Rel deficient NK cells and restored their cytotoxic function. Our results show a previously unknown role of c-Rel in transcriptional regulation of perforin and granzyme B expressions and control of NK cell cytotoxic function.